New bradoriid arthropods from the Giles Creek Dolostone (Cambrian Series 3, Stage 5; Templetonian), Amadeus Basin, central Australia - Smith, Patrick M.; Brock, Glenn A.; Paterson, John R.; Topper, Timothy P. (2014)
A new assemblage of bradoriids is reported from the Giles Creek Dolostone (Cambrian Series 3, Stage 5; Templetonian) in the Ross River Gorge area, NE Amadeus Basin, central Australia. One new genus and four new species are described: Annge iperte gen. et sp. nov., Flemingopsis anteriospinata sp. nov., Monasterium ferox sp. nov. and Mongolitubulus tunpere sp. nov. Only M. tunpere sp. nov. may have been described previously from adjacent basins. This study provides the first systematic description of a Cambrian bradoriid assemblage from the Amadeus Basin.